2017
DOI: 10.31234/osf.io/fmjks
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cross-dimensional magnitude interaction is modulated by representational noise: Evidence from space-time interaction

Abstract: Magnitudes along different dimensions (e.g., space and time) tend to interact with each other in perception, with some magnitude dimensions more susceptible to cross-dimensional interference than others. What causes such asymmetries in cross-dimensional magnitude interaction is being debated. The current study investigated whether the representational noise of magnitudes modulates the (a)symmetry in space-time interaction. In three experiments using different formats of length, we showed that dynamic unfilled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Such a finding is consistent with the conclusion of Cai and Connell (2015) that the interaction between space and time is shaped by the acuity with which space is perceived and memorized. Indeed, in another study (Wang & Cai, 2017), we provided additional evidence that the amount of interference a dimension is susceptible to is proportionally related with the memory noise that dimension has (a point we will return to in the general discussion).…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Such a finding is consistent with the conclusion of Cai and Connell (2015) that the interaction between space and time is shaped by the acuity with which space is perceived and memorized. Indeed, in another study (Wang & Cai, 2017), we provided additional evidence that the amount of interference a dimension is susceptible to is proportionally related with the memory noise that dimension has (a point we will return to in the general discussion).…”
Section: Discussionmentioning
confidence: 91%
“…As discussed earlier, when space is presented visually as filled length, it biases time but itself is not biased by time (e.g., Casasanto & Boroditsky, 2008); in contrast, when space is haptically perceived, it is susceptible to interference from time (Cai & Connell, 2015). Wang and Cai (2017) also showed that space-time interaction also hinges on length format: while filled lengths (e.g., in the form of a solid line) unilaterally affects concurrent durations, unfilled lengths (e.g., demarcated empty spatial intervals) and concurrent durations have a reciprocal influence on each other. They further showed that these different patterns of interaction is due to the fact that unfilled lengths afford noisier memory representations than filled lengths;…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations